REMOVAL OF NATURAL ORGANIC MATTER USING ELECTROCOAGULATION AS A FIRST STEP FOR DESALINATION OF BRACKISH WATER - Wasinton Simanjuntak; Irwan Ginting; Kamisah D. Pandiangan (Indonesian Journal of Chemistry, 2011)
In the present study, electrocoagulation method was employed to remove natural organic matter from brackish water. This study explores the potential of brackish water as a source of potable water. Two electrochemical variables, potential and contact time, were tested to determine their effect on the treatment efficiency defined in terms of the reduction of the absorbance at the wavelength of 254 nm (A254). Both potential and contact time were found to influence the removal efficiency of the method, and the best result was obtained from the experiment using the potential of 8 V and contact time of 60 min, resulting in 69.5% reduction of the absorbance. Very clean treated water was produced with much lower conductivity (12.06 mS/cm) as compared to that obtained for the sea water sample from a location near to the sampling site (133.9 mS/cm).